Implementation of Audio-Visual Media On The Language Skills Of Children Aged 5-6 Years In PAUD Mekar Harum I North Lombok - Rahmat, Mulyana; Mahendra, Juandra Prisma; Alawiyah, Tuti (Peneliti.net, 2025)
This study aims to analyze the learning of Audio Visual Media on the language skills of PAUD Mekar Harum I students in the 2024/2025 academic year. This research was conducted in class B2 with 12 students consisting of 6 boys and 6 girls with an age range of 5-6 years. The focus of this research is on the learning process of audio-visual media and language skills, especially on students' speaking skills during the audio-visual media learning process. This research uses a qualitative approach with an exploratory type of field research. Based on the results of the study that in the learning process, there are 3 stages carried out by the teacher, namely the preparation, implementation and assessment/evaluation stages. Preparatory activities are carried out by preparing lesson plans, preparing tools and media. At the implementation stage, the activity process is carried out with three stages, namely opening, core, and closing, while at the learning assessment/evaluation stage it is carried out by giving an assessment according to the results of students' abilities on the assessment sheet about students' attitudes, knowledge and skills. The supporting factors of learning include the availability of facilities, support from the principal, the availability of learning resources, and the teacher's ability to use audio-visual media while the inhibiting factors in the application of audio-visual media are determining videos according to the theme and interests of children, and the occurrence of internet network disruptions. The impact of the application of audio visual media on children's language skills is that it can improve the ability to speak articulation / pronunciation, improve the ability to speak in compiling sentences into a story, and help children in expressing their feelings. The advantages of applying audio visual media are durable and long-lasting, making the video screen on the TV larger in size, saving teacher energy in explaining, providing variations in learning methods, material is easy to understand, and can improve language skills in children. While the shortcomings of the application of audio visual media are cellphone connections to TVs that are often disconnected and cellphone audio visual media connected to this TV need extra care to be safe, not to fall and break.